Retrospective analysis of the impact of human papillomavirus infection in the male genital tract on sperm: from a single center - Sun, Huanxin; Tang, Xiao; Tong, Lingling; Liu, Qianqi; Kuang, Wei; Wang, Wei; Zhang, Su; Wang, Cheng (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study primarily aimed to investigate human papillomavirus (HPV) infection in males and to evaluate its effect on semen parameters, fertility and partner HPV infection status.MethodsA total of 624 men who visited the West China Second Hospital of Sichuan University between October 1, 2019, and September 30, 2023, were included. HPV DNA was detected in exfoliated cells from the male genitalia using polymerase chain reaction (PCR) and reverse membrane hybridization to analyze the relationship between HPV infection and semen parameters. Furthermore, we retrospectively reviewed medical records of the participants and their partners to collect data on HPV infection and fertility outcomes.ResultsThe overall prevalence of HPV infection was 43.8% (273/624), with single-genotype infections accounting for a significantly higher proportion (59.3%, 162/273) than multiple-genotype infections (40.7%, 111/273). The five most prevalent HPV genotypes were HPV52, HPV16, HPV51, HPV58, and HPV42. High-risk (HR) genotypes accounted for most infections (79.5%, 217/273). Among 377 men who underwent semen analysis, HPV-positive individuals exhibited significantly reduced sperm motility and normal morphology compared to HPV-negative individuals (p<0.001). Furthermore, HPV infection was associated with increased sperm DNA fragmentation (p=0.007). Males co-infected with Ureaplasma urealyticum and Chlamydia trachomatis showed significantly lower total sperm counts (×106) (p=0.025) and DFI values (p=0.038) than those without co-infection. Partner data were available for 416 of the 624 men. In these couples, female HPV infection was significantly associated with male HPV status (p=0.038), particularly for HR-HPV (p=0.049). Male HPV-negative status was associated with a higher rate of normal fertility (p<0.001).ConclusionOur findings indicate that male genital HPV infection is common and may adversely affect semen quality, fertility, and increase the risk of HPV transmission to sexual partners.